2019
DOI: 10.3390/ijerph16245032
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Non-Branded Foods Placed in Cartoons on Children’s Food Choices through Type of Food, Modality and Age

Abstract: Cartoons are among the most consumed media products by children, especially those at a young age. While branded food placements are not allowed in animated series, non-branded food placements are prevalent. However, little is known about the effects that these food placements might have on children’s eating preferences. In an experimental study with 124 children (51.6% girls, age range: 7–11, Mage = 9.24, and SD = 1.19), 62 children in the experimental condition were exposed to 16 food placements in cartoons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 55 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…The results also show that, as children grow up, they might be less persuaded by foods embedded in entertainment media [58]. In addition, it might be possible that it is the interaction of several variables that makes foods embedded in entertainment media more impactful: the combination of low nutritional value foods targeted to children younger than 9 years old [29].…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The results also show that, as children grow up, they might be less persuaded by foods embedded in entertainment media [58]. In addition, it might be possible that it is the interaction of several variables that makes foods embedded in entertainment media more impactful: the combination of low nutritional value foods targeted to children younger than 9 years old [29].…”
Section: Discussionmentioning
confidence: 81%
“…In total, 1624 unique studies were identified through database searches, of which, 26 [13,22,23,26,29,30,39,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] were deemed eligible for inclusion. Compared to the studies included in similar, previous systematic reviews [62] and meta-analyses [17][18][19][20][21], the present meta-analysis contained 12 extra studies [22,23,26,29,30,49,51,52,55,56,58,60]. The PRISMA flow diagram is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations